A Novel Transcript Isoform of TBK1 Negatively Regulates Type I IFN Production by Promoting Proteasomal Degradation of TBK1 and Lysosomal Degradation of IRF3 - Zhang, Jie; Wu, Xiao Man; Hu, Yi Wei; Chang, Ming Xian (Frontiers in Immunology, 2020)
TANK-binding kinase 1 (TBK1), an IKK-related serine/threonine kinase, is pivotal for the induction of antiviral type I IFNs by TLR and RLR signaling pathways. In a previous study, we demonstrated that TBK1 spliced isoforms (TBK1_tv1 and TBK1_tv2) from zebrafish were dominant negative regulators in the RLR antiviral pathway by targeting the functional TBK1-IRF3 complex formation. In this study, we show that the third TBK1 isoform (namely TBK1_tv3) inhibits zebrafish type I IFN production by promoting TBK1 and IRF3 degradation. First, ectopic expression of TBK1_tv3 suppresses poly(I:C)- and SVCV-induced type I IFN response, and also inhibits the upregulation of IFN promoter activities stimulated by RIG-I, MDA5, MAVS, TBK1 and IRF3. Second, TBK1_tv3 targets TBK1 and IRF3 to impair the formation of TBK1 dimer, TBK1-IRF3 complex and IRF3 dimer. Notably, TBK1_tv3 promotes the degradation of TBK1 through the ubiquitin-proteasome pathway, and the degradation of IRF3 through the autophagy-lysosomal pathway. Further analysis demonstrates that TBK1_tv3 promotes the degradation of TBK1 for K48-linked ubiquitination by targeting the K251，K256 and K271 sites of TBK1. Collectively, our results suggest a novel TBK1 isoform-mediated negative regulation mechanism, which serves to balance the production of type I IFNs and ISGs.